HUBUNGAN PENGELOLAAN KELAS DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD SE-GUGUS I KECAMATAN MARPOYAN DAMAI PEKANBARU - Jesica, Lia; Witri, Gustimal; Lazim, Lazim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
ABSTRACTThis research aims to find out the correlation between classroom management and mathematics learning outcomes of 5th grade students of elementary school cluster 1, Marpoyan Damai Sub-district, Pekanbaru. This is a qualitative research which applies korelasional method. The samples of this research are teachers and 5th grade students chosen by using snowball sampling technique. The data were collected by using observation sheet, interview guidelines, and documentation. Meanwhile, the students’ mathematics learning outcomes data were taken from mathematics average score of 5th grade students. The data were analyzed through three steps namely; data reduction, data display, conclusion drawing and verifying. According to data analysis, it was found out that there were correlation between classroom management and mathematics learning outcomes where it could be seen from the increasing of students’ average score. Hence, it can be stated that teachers had fulfilled the principle of classroom management. Teachers also had implemented the factors that influence classroom management quite well. However, it could not be denied that there was still sub-indicator that teachers could not implement such as inappropriate space of classroom management. Based on research results, it can be concluded that the better the classroom management is implemented, the better the students’ mathematics learning outcomes will be.